Upaya Meningkatkan Pemahaman Toleransi Siswa Melalui Penerapan Model Problem Based Learning (PBL) Berbasis Isu Multikultural pada Pembelajaran Pendidikan Pancasila di Kelas XI SMAN 1 Sidemen - Agung Kurniawan; Nur Wahyu Rochmadi; Didik Sukriono; Siti Awaliyah (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Understanding tolerance cannot be formed solely through oneway value transmission; rather, it requires a learning process that engages students in critical reasoning toward the reality of social plurality. This activity was implemented as an effort to strengthen students’ understanding of tolerance through the application of a Problem Based Learning (PBL) model based on local multicultural issues in Civic Education learning in class XI B of SMAN 1 Sidemen. The activity aimed to improve students’ tolerance understanding (civic knowledge) through a pedagogical intervention grounded in socio-cultural problems closely related to students’ daily lives.The implementation of this activity used a Classroom Action Research (CAR) design based on the spiral model of Kemmis and McTaggart, conducted in two participatory-reflective cycles. Quantitative data were collected using an essay-based cognitive test instrument with a rubric scale covering indicators C2–C5, while qualitative data were obtained through observation sheets of learning syntax implementation. The results of the activity show that exposure to ill-structured problems derived from local social dynamics, such as local–migrant relations and the sensitivity of the caste stratification system, was able to trigger cognitive dissonance, which contributed to the improvement of students’ reasoning quality. This is evidenced by an increase in the average learning outcomes from 58.12 in the Pre-Cycle stage to 72.50 in Cycle I, and reaching 83.15 in Cycle II. The classical completeness percentage also increased from 43.75% to 87.50%, exceeding the predetermined success indicator of ≥80%. Overall, the implementation of a PBL model based on local multicultural issues proved effective in dismantling learning misconceptions, reducing cultural bias, and shifting students’ learning orientation from textual memorization toward analytical thinking and problem-solving skills grounded in Pancasila values.